THE HEALTH PRESERVATION IN A CONSUMER SOCIETY THROUGH THE PRISM OF THE DIALECTIC CATEGORIES OF “ESSENCE” AND “PHENOMENON” - Dobryden, Oksana V. (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2019)
Introduction. During each historical period, the issue of health preservation acquires new essence characteristics which are determined by the transformations of social systems. Under the modern overconsumption society circumstances, put on the current socio-economic and political situation in Ukraine, the problem of internal nature and systemic inter-influences of such phenomenon as health preservation becomes extremely stressed and urgent. Purpose: to analyze the semantic features of the dialectical categories of essence and phenomenon in the context of the personal health-preserving activity of the individual in today’s over-consumption society. Methods. Studying such phenomena as health and consumer society is interdisciplinary. Pluralism of approaches allows us to develop an effective theoretical and methodological basis in order to form alternative socio-philosophical views in the context of consumer risk reduction. The methodological basis of this article is a comparative approach which made it possible to match individual phenomena in health preservation in today’s consumption society. Results. Health preservation is often equated with caring for one’s physical and mental health, with healthy eating habits and sports. It is clear that for regular caregiving, the person must be motivated and characterized by willpower, self-discipline, and awareness of a healthy lifestyle. In other words, health preservation, as a process and as a phenomenon as a whole is extremely positive and beneficial in its essence. However, this positive characteristic of health preservation as a phenomenon would be real only if the person were not involved in other processes and phenomena that fundamentally change its positive nature. In the socio-cultural space of a consumer society, we have the opportunity to observe the distortion of the productive nature of health preservation, which is outlined not only by people’s desire to be healthy, and careful treatment of themselves but also by the artificially created motives and externally stimulated needs of their health-preserving activity. Conclusion. In a society of consumption, people’s health-preserving activity is in the space of increasing risks that are not being considered to be a threat because they are perceived as the satisfaction of needs and realization of desires. As a result, the substitution of concepts in the phenomenon of health preservation and distortion of its positive essence is taking place.